Event-free survival in patients with early HER2-positive breast cancer with a pathological complete response after HER2-targeted therapy: a pooled analysis - Swain, Sandra M.; Macharia, Harrison; Cortes, Javier; Dang, Chau; Gianni, Luca; Hurvitz, Sara A.; Jackisch, Christian; Schneeweiss, Andreas; Slamon, Dennis; Valagussa, Pinuccia; Du Toit, Yolande; Heinzmann, Dominik; et al. (Cancers, 2022)
The standard-of-care for patients with pathological complete response (pCR) after neoadjuvant human epidermal growth factor receptor 2 (HER2)-targeted therapy plus chemotherapy is continuation of HER2-targeted therapy in the adjuvant setting. Our objective was to evaluate risk of recurrence or death in these patients and determine if outcomes differed by the HER2-targeted regimen received in each setting. We analyzed patient-level data from five randomized trials evaluating trastuzumab, pertuzumab, or both as part of systemic neoadjuvant and adjuvant therapy for HER2-positive early breast cancer, and assessed event-free survival (EFS) in 1763 patients. Patients with pCR had decreased risk of an EFS event versus those with residual disease (unadjusted hazard ratio [HR] = 0.35; 95% confidence interval [CI]: 0.27-0.46). Regardless of pCR status, after adjusting for baseline factors, reduction in EFS event risk was greater in patients administered pertuzumab/trastuzumab in both settings versus those administered only trastuzumab in both settings (HR = 0.36; 95% CI: 0.26-0.49), or pertuzumab/trastuzumab in the neoadjuvant setting and only trastuzumab in the adjuvant setting (HR = 0.67; 95% CI: 0.47-0.96). Patients with pCR had longer EFS than those with residual disease. Patients treated with pertuzumab/trastuzumab in both the neoadjuvant and adjuvant settings had the lowest risk of breast cancer recurrence.
Gesehen am 18.01.2023